Classifiers : a typology of noun categorization devices - Aĭkhenvalʹd, A. I͡U. (Aleksandra I͡Urʹevna) (Oxford studies in typology and linguistic theory., 2000)
This text offers a cross-linguistic account of classifiers. Its range of exemplification includes major and minor languages from every continent and several of the examples are from the author's own fieldwork.